À utilização do programa crocodile clips como um facilitador do processo de ensino aprendizagem em eletrodinâmica - Gomes, André da Paixão (2016)
In the text the author presents a differentiated alternative for assistance in the construction of knowledge. Such work was chosen due to the fact that despite 40 years of progress in developing techniques to assist in the cognitive development of the study, many of these techniques are not used. In order to show a possible solution to this problem it was selected a software that allows an optimization of the time required for the presentation of electrodynamics content in a satisfactory and playful way.